Multidrug-Resistant Strain ExPEC Isolat Asal Puyuh (Coturnix coturnix japonica) - Wahyu Prihtiyantoro; Agus Purnomo; Sudarisman .; Khusnan . (Jurnal Sain Veteriner, 2023)
AbstractExtraintestinal Escherichia coli (ExPEC) causes colibacillosis in poultry, including quail. ExPEC is a pathogenic E. coli that causes colibacillosis outside the gastrointestinal tract of poultry, in the form of peritonitis, pericarditis, salpingitis, synovitis, osteomyelitis, septicemia, pneumonitis, nephritis, pleurisy, proventriculitis and ventriculitis. In poultry farming antibiotics are used to promote growth and egg production, prevention and treatment of bacterial infections. Antibiotic resistance is a new problem that arises in poultry farming. In this study, 24 isolates of ExPEC strain from quail were used. These isolates did not differentiate sorbitol in the MacConkey (SMAC) sorbitol test assay. Antibiotic resistance was tested based on the inhibition of bacterial growth on Muller Hinnton Agar (MHA) media. 10 types of antibiotics were used to observe their resistance in all isolates. Resistance to Amikacin (87.5%), Ampicillin (87.5%), Ciprofloxacin (100%), Clindamycin (95.83%), Cefoxacin (25.0%), Doxycycline (87.5%), Erythromycin (100%), Gentamicin (95.83%), Penicillin (95.83%) and Tetracycline (83.3%). The isolates had multidrug-resistance between 3 to 10 types of antibiotics. This study showed that ExPEC isolates from quail were resistant to the type of antibiotics tested, so that the use of antibiotics in quail culture should be limited to reduce and prevent the emergence of new antibiotic resistance. Keyword: Escherichia coli, sorbitol-negative, quail, antibiotics resistance